Land Management for Agricultural Entrepreneurship Development: Farmers’ Perspective from Udayapur, Nepal - Rai , Ashish; Devkota , Niranjan; Bhandari, Udbodh; Paudel, Udaya Raj (Asian Journal of Agriculture and Rural Development, 2020)
This study aims to explore farmers’ perspectives on land management for agricultural entrepreneurship in Udayapur, Nepal. The research is based on cross-sectional explanatory research design, and a structured questionnaire was administered for collecting the data from 297 farmers in Tiryuga, Chudandhigadhi, and Belaka municipalities in Udayapur. The results were derived with the help of descriptive and inferential analysis using STATA. The results show that agricultural training and market information play significant roles in gaining awareness about agricultural entrepreneurship and ideas on land management. Agricultural training, credit facilities, and market information have a positive relationship with an awareness of agricultural entrepreneurship and ideas on land management. In contrast, the age, land size, crop cycle, credit facility and agricultural subsidy have a negative relationship with them. This study suggests the need for increasing and enhancing the knowledge for farmers about agricultural entrepreneurship and proper land management in Nepal. The outcome of this study remains significant mostly in developing nations like Nepal and even in the developed ones to feed the growing population’s increasing food demand, as land area is limited on earth and the population living on it is swelling.